2003
DOI: 10.1051/limn/2003021
|View full text |Cite
|
Sign up to set email alerts
|

Is the rhythm of vertical migration of Daphnia longispina circadian or simply nycthemeral ?

Abstract: From an ecological viewpoint, diel vertical migration (DVM) of zooplankton is an adapted response to environmental factors. DVM coincides with changes in light intensity, but persists also under constant illumination conditions. This fact suggests the existence of an internal clock. In Daphnia longispina, it could be located in the eye. Indeed, the spatial distribution of the pigments containing in the eye ommatidia exhibits significant changes over time when Daphnia are kept under light/dark (LD) conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Additionally, we cannot completely exclude the possibility that the structure of the TTFL of Daphnia differs from those proposed for insects that can run free under LL and DD conditions. Moreover, such reasoning may implicate a lack of diel vertical migrations (DVMs) of Daphnia longispina reared under special LD conditions; when animals were exposed exclusively to blue light during the light period, they became arrhythmic, thus behaving like most animals in LL (Cellier‐Michela et al., ). If the oscillator structure of Daphnia was similar to those of insects, it would be strongly synchronized by the Zeitgeber under blue LD conditions, i.e., the light with wavelengths corresponding to the blue light that directly affects its mechanism via the photoreactive CRY 1 protein (Suri et al., ; Emery et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we cannot completely exclude the possibility that the structure of the TTFL of Daphnia differs from those proposed for insects that can run free under LL and DD conditions. Moreover, such reasoning may implicate a lack of diel vertical migrations (DVMs) of Daphnia longispina reared under special LD conditions; when animals were exposed exclusively to blue light during the light period, they became arrhythmic, thus behaving like most animals in LL (Cellier‐Michela et al., ). If the oscillator structure of Daphnia was similar to those of insects, it would be strongly synchronized by the Zeitgeber under blue LD conditions, i.e., the light with wavelengths corresponding to the blue light that directly affects its mechanism via the photoreactive CRY 1 protein (Suri et al., ; Emery et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we evaluate whether there is a circadian rhythm in feeding behavior in Daphnia dentifera , a dominant primary consumer in North American temperate lakes. Prior studies have indicated that Daphnia have core clock genes and circadian expression of melatonin, immune, and sensory genes (Cellier-Michel et al, 2003; Bentkowski et al, 2010; Bernatowicz et al, 2016; Schwarzenberger and Wacker, 2015; Schwarzenberger et al, 2020, 2021). Daphnia are a model system for studying circadian rhythms in feeding behavior because they reproduce clonally, making individuals genetically identical, and quantifying individual feeding rates is relatively simple (Hite et al, 2020).…”
mentioning
confidence: 99%
“…Many Daphnia clones are migrating to deeper water layers during the day in order to escape UV light and fish predation (Loose and Dawidowicz, 1994;Rhode et al, 2001;Ekvall et al, 2015); thus, they are confronted with diurnal changes in food quality and quantity. In Daphnia, the involvement of the clock in diel vertical migration (DVM) is likely (Cellier-Michel et al, 2003), especially because DVM is inhibited by the application of exogenous melatonin (Bentkowski et al, 2010). Since food quantity often is high at the surface of freshwater bodies (where Daphnia are situated during night) and low in deeper water levels (to which Daphnia sink to during day) a circadian expression and activity of digestive enzymes is expected.…”
Section: Introductionmentioning
confidence: 99%